Co-remediation of Pb Contaminated Soils by Heat Modified Sawdust and Festuca arundinacea - Zhang, Yan (Sci Rep, 2020)
This research aimed to explore the potential and mechanism of heat modified sawdust combined with Festuca arundinacea for the remediation of Pb-contaminated soil. We determined Pb concentration and biochemical indices in plants and soils, analyzed microbial communities in soil, and studied Pb distribution in subcellular and tissues. Under co-remediation of 5% material addition and Festuca arundinacea, the concentration of Pb in soil decreased. Pb toxicity of Festuca arundinacea was alleviated by 2% material addition through the promotion of plant growth and reduction of oxidative stress. In addition, soil enzyme activities and microbial community in contaminated soil were promoted by the application of co-remediation. Festuca arundinacea cell wall accumulated a large amount of Pb, and the addition of material promoted the accumulation of Pb in Festuca arundinacea root. The concentration of Pb in the shoot of the plant treated with 2% material was higher than that of the plant treated with 5% material, and the damage of Festuca arundinacea leaves was lower under 2% treatment. The combination of heat modified sawdust and Festuca arundinacea promoted the adsorption of Pb by plants, and protected the growth of plants.